Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
Lời giải:
a)
\(\cos ^2a+\cos ^2b+\cos ^2a\sin ^2b+\sin ^2a\)
\(=(\cos ^2a+\sin ^2a)+\cos ^2b+\cos ^2a\sin ^2b\)
\(=1+1-\sin ^2b+\cos ^2a\sin ^2b\)
\(=2-\sin ^2b(1-\cos ^2a)=2-\sin ^2b\sin ^2a\)
b)
\(2(\sin a-\cos a)^2-[(\sin a+\cos a)^2+\sin a\cos a]\)
\(=2(\sin ^2a-2\sin a\cos a+\cos ^2a)-[\sin ^2+2\sin a\cos a+\cos ^2a+\sin a\cos a]\)
\(=2(1-2\sin a\cos a)-(1+3\sin a\cos a)\)
\(=1-7\sin a\cos a\)
c)
\((\tan a-\cot a)^2-(\tan a+\cot a)^2\)
\(=\tan ^2a+\cot ^2a-2\tan a\cot a-(\tan ^2a+\cot ^2a+2\tan a\cot a)\)
\(=-4\tan a\cot a=-4\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,1-sin^2\alpha=cos^2\alpha\)
\(b,\left(1-cos\alpha\right)\left(1+cos\alpha\right)=1-cos^2\alpha=sin^2\alpha\)
\(c,1+sin^2\alpha+cos^2\alpha=1+1=2\)
\(d,sin\alpha-sin\alpha.cos^2\alpha=sin\alpha.\left(1-cos^2\alpha\right)=sin\alpha.sin^2\alpha=sin^3\alpha\)
\(e,sin^2\alpha+cos^2\alpha+2sin^2\alpha.cos^2\alpha\)
\(=1+2sin^2\alpha.cos^2\alpha\)
![](https://rs.olm.vn/images/avt/0.png?1311)
đáp án :
a) \(cos^2\alpha\)
b) 1
c) \(sin^2\alpha\)
d) \(sin^2\alpha\)
e) 2
g) 1
h) \(sin^3\alpha\)
i) \(sin^2\alpha\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(A=\sin^6\alpha+cos^6\alpha+3\sin^2\alpha\cos^2\alpha\left(\sin^2\alpha+\cos^2\alpha\right).\)vì\(\sin^2\alpha+\cos^2\alpha=1\)
\(=\left(\sin^2\alpha+\cos^2\alpha\right)^3=1^3=1\)
\(B=2\left(\cos^2\alpha+\sin^2\alpha\right)=2.1=2\)
\(C=\frac{-4\cos\alpha\sin\alpha}{\sin\alpha\cos\alpha}=-4\)
\(cosa+sina=m\)
=>\(\left(cosa+sina\right)^2=m^2\)
=>\(1+2\cdot sina\cdot cosa=m^2\)
=>\(2\cdot sina\cdot cosa=m^2-1\)
\(P=\left|cosa-sina\right|\)
\(=\sqrt{\left(cosa-sina\right)^2}\)
\(=\sqrt{cos^2a+sin^2a-2cosa\cdot sina}\)
\(=\sqrt{1-\left(m^2-1\right)}=\sqrt{2-m^2}\)